2016
DOI: 10.1039/c6ee01514j
|View full text |Cite
|
Sign up to set email alerts
|

Forthcoming perspectives of photoelectrochromic devices: a critical review

Abstract: This review article explores the historical development and the recent progress of photoelectrochromic devices (PECDs), evaluating on the bases of components evolution their future perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 255 publications
(240 reference statements)
2
72
0
2
Order By: Relevance
“…Predictions about future developments are notoriously difficult, but here follow some perspectives on multifunctionality in conjunction with electrochromics, which may become a key issue [173,174]. Thus it is possible to combine energy generation [175,176], energy storage [177][178][179][180][181], or light-emission [182] with electrochromism, and another aspect of multifunctionality regards "dual-band" EC devices that are capable of separately modulating luminous radiation and near-infrared solar radiation [54,[183][184][185][186][187]. Still another possibleperhaps even likely-future development of EC technology concerns thermochromic (temperature-dependent) control of solar energy throughput, which can be added to electrochromism via VO 2 -based nanoparticles [188][189][190] in the electrolyte in analogy with the application of nanoparticles discussed in Sec.…”
Section: Some Conclusion and Perspectivesmentioning
confidence: 95%
“…Predictions about future developments are notoriously difficult, but here follow some perspectives on multifunctionality in conjunction with electrochromics, which may become a key issue [173,174]. Thus it is possible to combine energy generation [175,176], energy storage [177][178][179][180][181], or light-emission [182] with electrochromism, and another aspect of multifunctionality regards "dual-band" EC devices that are capable of separately modulating luminous radiation and near-infrared solar radiation [54,[183][184][185][186][187]. Still another possibleperhaps even likely-future development of EC technology concerns thermochromic (temperature-dependent) control of solar energy throughput, which can be added to electrochromism via VO 2 -based nanoparticles [188][189][190] in the electrolyte in analogy with the application of nanoparticles discussed in Sec.…”
Section: Some Conclusion and Perspectivesmentioning
confidence: 95%
“…[6] For their potential impact on energy supply and saving by reducing cooling and heating loads and the demand for electric lighting, smart windows are expected to become important architectural components of future buildings. [6] At the same time, the use of liquid or gel electrolytes poses safety problems and requires a more complex sealing procedure and an additional lamination step of the two glass electrodes, limiting the speed of manufacturing process and increasing costs. [10] To date, the most part of EC devices (ECDs) appeared so far in literature are based on liquid or gel electrolytes, which confer relevant limitations mainly due to defects in homogeneity of coloration, dark spots, and pinholes for the inhomogeneous distribution of the electric field applied, peripheral leakage for inefficient sealing, and, especially, a limited durability and lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In addition, they offer outstanding features of no leakage, high flexibility, lightweight, and good compatibility with electrode materials, making them suitable for scale up to large area and for the integration with other optoelectronic systems, such as a photovoltaic cell or organic light emitting diode. [6,15] Furthermore, the most part of SPEs and gel electrolytes can be involved in degradative processes promoted by parasitic side reactions with air or moisture [18] and can be subjected to photooxidative degradation by UV radiation or catalytic processes with the consequent discoloration of the surface and extensive mechanical damages, thus compromising their aesthetical and functional requirements. [6,15] Furthermore, the most part of SPEs and gel electrolytes can be involved in degradative processes promoted by parasitic side reactions with air or moisture [18] and can be subjected to photooxidative degradation by UV radiation or catalytic processes with the consequent discoloration of the surface and extensive mechanical damages, thus compromising their aesthetical and functional requirements.…”
Section: Introductionmentioning
confidence: 99%
“…A specific study by Boyce et al [20], found that the minimum acceptable glazing transmittance for office buildings should fall within the range between 25% and 38%. This is a fundamental parameter for EC glazing, semitransparent PVs and photo-electrochromic devices [21][22][23]. Moreover, a specific survey showed that effective smart glazing for building integration should be capable to switch their T vis from 50-70% in the bleached Energies 2020, 13, 1449 4 of 17 state to less than 10-20% in the colored state [24].…”
Section: A Short Glossary Of the Main Parameters Used For The Charactmentioning
confidence: 99%